PRAANGGAPAN DALAM FILM LITTLE WOMEN KARYA GRETA GERWIG (SUATU ANALISIS PRAGMATIK) - Pongoh, Julianti Sasmita; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research is entitled â€œPraanggapan Dalam Film Little Women Karya Greta Gerwigâ€. This research attempts to investigate the pragmatics presupposition in the film Little Women by Greta Gerwig. In this research, the researcher attempts to identify, classify and analyze the types and meanings of presupposition in the film Little Women by Greta Gerwig. The data were collected from the film Little Women by Greta Gerwig. In identifying, classifying and analyzing the data, the researcher uses the theory of Yule (1996). The result shows that there are five types of presupposition and their function applied by the characters in their dialogues. First, existential presupposition consist of 393 utterances that presuppose the existence of an entity. Second, factive presupposition consist of 60 utterances that presuppose information that is presumed to be something real or a fact. Third, lexical presupposition consist of 23 utterances that presuppose other meanings or implied meanings that are understood. Fourth, structural presupposition consist of 132 utterances that presuppose information regarding something in speech in the form of interrogative sentences or 5W1H structures, this can be seen in interrogative sentences which are conventionally interpreted with question words. Fifth, counterfactual presupposition consist of 11 utterances that presuppose not only something is not true but also contradicts the existing reality. Sixth, non-factive presupposition presuppose that something is assumed to be unreal consisting of 0 utterances or no data of this type of presupposition found in the film Little Women by Greta Gerwig. The most frequent presupposition in this film is Existential Presupposition which consists of 393 utterances. This research is expected to give contributions to the development of linguistic studies, particularly in Pragmatic analysis. It is also expected to help the readers to have knowledge of the pragmatic presupposition.Keywords: Presupposition, Pragmatics, Film Little Women